The Role of Organizational Commitment Job Satisfaction, and Organizational Culture on Work Productivity: Case Study of Indonesian Migrant Worker Placement Companies in West Nusa Tenggara - Taufik Hidayat Pulungan; Abdul Aziz Bagis; Santi Nururly (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the moderating role of organizational culture on the influence of organizational commitment and job satisfaction on work productivity. The research employs a causal-associative design with a quantitative approach. Data were collected using a census method involving 86 respondents from 13 companies within the Indonesian Migrant Worker Placement Centers (P3MI) in West Nusa Tenggara (NTB). The data analysis technique applied was PLS-SEM using Smart-PLS version 3 software. The findings indicate that organizational commitment has a significant positive effect on work productivity, and job satisfaction also has a significant positive effect on work productivity. Furthermore, organizational culture strengthens the influence of organizational commitment on work productivity, as well as the influence of job satisfaction on work productivity. Among these factors, job satisfaction emerges as a particularly critical determinant in enhancing employee productivity. Therefore, companies need to consistently maintain and improve managerial practices that foster job satisfaction, such as providing fair rewards, creating opportunities for career development, and building a supportive organizational culture along with a conducive work environment.